The diagnostic yield of CT-guided percutaneous lung biopsy in solid organ transplant recipients - Hsu, Joe L. (2012)
BACKGROUND: Despite the widespread use of computed tomography (CT)-guided percutaneous lung biopsy (PLB) in immunocompetent patients, the diagnostic yield and safety in solid organ transplant (SOT) recipients is unknown. The purpose of this investigation was to determine the test performance of CT-PLB in SOT recipients. METHODS: We performed a 10-year single-center, retrospective analysis among heart, lung, kidney and liver transplant recipients. We included all adult patients who underwent a PLB of a parenchymal lung nodule following their transplantation. RESULTS: Within the study period, 1754 solid organ transplants were performed of which 45 biopsies met study criteria. Overall the incidence of PLB in SOT was 3%. PLB established a diagnosis in 24 out of 45 cases. The yield of PLB was better for combined biopsy technique (fine needle aspiration biopsy (FNAB) and core biopsy (CB)) than for FNAB alone (odds ratio (OR): 4.2, 95% confidence interval (CI): 1.2, 15.6), and for lesions that were malignant (OR: 10.0, 95% CI: 1.8, 75.4) or caused by an invasive fungal infection (OR: 5.0, 95% CI: 1.1, 27.9). Complications occurred in 13% (6/45) of patients. CONCLUSION: CT-guided PLB is a safe modality that provides a moderate yield for diagnosing pulmonary nodules of malignant or fungal etiology in SOT recipients.